Blackened faces and a Veiled Woman: The Early Korčula Moreška - Čale Feldman, Lada (Array, 2004)
The purpose of the article is twofold: to develop a coherent account of the early history of the moreška in Korčula and its possible antecedents elsewhere: and to show that in Korčula, too, a hidden transcript of resistance to external rule was insinuated into the imported narrative of Turks, Moors, and Christians.